DhMYB2 and DhbHLH1 regulates anthocyanin accumulation via activation of late biosynthesis genes in Phalaenopsis-type Dendrobium - Wang, Yachen; Yin, Hantai; Long, Zongxing; Zhu, Wenjuan; Yin, Junmei; Song, Xiqiang; Li, Chonghui (Frontiers in Plant Science, 2022)
Phalaenopsis-type Dendrobium is a popular orchid with good ornamental and market value. Despite their popularity, molecular regulation of anthocyanin biosynthesis during flower development remains poorly understood. In this study, we systematically investigated the regulatory roles of the transcription factors DhMYB2 and DhbHLH1 in anthocyanins biosynthesis. Gene expression analyses indicated that both DhMYB2 and DhbHLH1 are specifically expressed in flowers and have similar expression patterns, showing high expression in purple floral tissues with anthocyanin accumulation. Transcriptomic analyses showed 29 differentially expressed genes corresponding to eight enzymes in anthocyanin biosynthesis pathway have similar expression patterns to DhMYB2 and DhbHLH1, with higher expression in the purple lips than the yellow petals and sepals of Dendrobium ‘Suriya Gold’. Further gene expression analyses and Pearson correlation matrix analyses of Dendrobium hybrid progenies revealed expression profiles of DhMYB2 and DhbHLH1 were positively correlated with the structural genes DhF3’H1, DhF3’5’H2, DhDFR, DhANS, and DhGT4. Yeast one-hybrid and dual‐luciferase reporter assays revealed DhMYB2 and DhbHLH1 can bind to promoter regions of DhF3’H1, DhF3’5’H2, DhDFR, DhANS and DhGT4, suggesting a role as transcriptional activators. These results provide new evidence of the molecular mechanisms of DhMYB2 and DhbHLH1 in anthocyanin biosynthesis in Phalaenopsis-type Dendrobium.